PENGGUNAAN LEAFLET TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP KELUARGA BARU - Sumiati, Sri (JURNAL MEDIA KESEHATAN, 2017)
A family is a small unite of society that hold an important role as nation asset.The quality family can be reached by doing a set of good planning. A family needsknowledge about a quality family. One of the approaches that can improve the society’swillingness to maintan of healthy is that by doing health promotion by using leafletmedia. This research aims to know the impact of health promotion toward theknowledge, behaviour, and the action taken by new family to reach a quality family. Thisresearch used quasi experimental by planning of non-equivalent control group design.The samples were the men and women that have just married that were 44 persons. Thefinding of the research showed that there were any impacts of health promotion by usingleaflet media toward the knowledge and the action of new family in reaching a qualityfamily. Therefore, there is a need to increase health promotion using leaflet media, so itcan improve the knowledge and the behaviour of the society about the quality family sothey can make it.